Neutrophil-to-lymphocyte ratio and perihematomal edema in patients with intracerebral hemorrhage - Catarina Pisco Martins (2022)
Background: The inflammatory response that follows intracerebral hemorrhage (ICH) is associated with worse outcome, but sparse data exist on the mechanistic link to that poor clinical recovery. We hypothesized that the intensity of systemic inflammation, measured by indexes such as the neutrophil-to-lymphocyte ratio (NLR), is related to increased perihematomal edema (PHE), thus leading to more neurological disability. Aims: To primarily investigate if NLR or classical systemic inflammatory response syndrome (SIRS) are related to the development of early PHE in ICH. Additionally, we compared the prognostic performance of NRL and SIRS for the functional outcome at 90 days. Methods: We designed a retrospective study including all patients with primary ICH admitted to our comprehensive stroke center in 2020 and those included in a previous cohort (2014-2015). Outcomes included absolute and relative PHE (rPHE), and edema extension distance (EED), measured with computed tomography scans performed at admission and 24 to 72 hours. The functional outcome was obtained from the modified Ranking Scale (mRS). Linear and logistic regression were used to estimate β coefficients or odds ratios (OR) and 95% confidence intervals (95%CI) for radiological and clinical endpoints. Results: We included 215 patients, 54% male sex with median (interquartile range) age of 73 (66-80). NLR and SIRS were not significantly associated with the early development of PHE either at admission or at 24-72 hours, except NLR at admission that was significantly related to rPHE at 24-72 hours (β= -4.78, CI -9.48 - -0.08). Furthermore, NLR at admission was significantly associated with worse functional outcome at 90 days (mRS 0-2, aOR=0.38, 0.17-0.87, P=0.021) while SIRS was not. The infection did not change results (P>0.05 for interaction). Conclusions: Inflammatory indexes predict long-term disability of ICH patients, an effect that cannot be explained by the development of early perihematomal edema. NLR is a superior prognostic factor compared to classical SIRS. More effort is needed to understand the mechanisms by which inflammation causes neurological injury in ICH.